Brief Report: Using Computer-Assisted Multiple Exemplar Instruction to Facilitate the Development of Bidirectional Naming for Children with Autism Spectrum Disorder. - Lee, Gabrielle T.; Hu, Xiaoyi; Jin, Ning (Journal of Autism & Developmental Disorders, 2021)
Bidirectional naming is an important ability which enables children to acquire listener and speaker behaviors through exposure to relevant word-object associations. Many children with autism spectrum disorder (ASD) or developmental delays do not demonstrate this ability and require systematic instruction. The purpose of the present study was to evaluate the efficacy of computer-assisted multiple exemplar instruction to facilitate bidirectional naming. Three 5-year-old Chinese boys with ASD participated in a multiple probe across three participants design. The results indicated that all three children's naming performance increased from pretest to posttest, supporting the potential practicality of the instructional system for use in applied settings.